Investigations on the Influence of Surface Textures on Optical Reflectance of Multi-crystalline Silicone (MC-Si) Crystal Surfaces-Simulations and Experiments - Ullattil, Sudeep; Kakkarath, Sudheesh; Viswambharanunnithan, Vinod; Ramannair, Suresh Padiyath (International Journal of Renewable Energy Development, 2022)
MC-Si is the most widely used material for making solar PV cells. In spite of the considerable research on improving the conversion efficiency of MC-Si solar PV cells still it remains well within the range of 15-20%. Optical reflectance being the major loss of incident solar energy, efforts are being made to reduce the optical reflectance of solar cell surfaces. Among the several methods proposed, creation of well-defined surface topography on the cell surface remains a promising option. Micro/nano level features with various dimensions and distributions have been created on MC-Si crystal surfaces using a femto-second pulsed laser and the influence of surface topography on optical reflectance in the incident light wave length of 350 – 1000 nm have been studied and compared with the simulation results obtained using OPAL2 software. Experimental results indicate that surface textures on the wafer surface lead to the reduction of optical reflectance in the range of 20-35% in comparison with plain surface. Width of micro grooves have less significant effect on the optical reflectance in comparison with pitch between the micro grooves. Best reduction in reflectance is exhibited by the texture having a groove width of 30 mm and a pitch of 100 mm. A post texturing etching operation is found to have detrimental effect on the ability of micro/nano level features in decreasing the optical reflectance in the preferred wavelength of solar spectrum due to the flattening of nano level features created within the micro grooves due to laser texturing.